UJI ANTAGONISME Trichoderma sp. TERHADAP Colletotrichum capsici PENYEBAB PENYAKIT ANTRAKNOSA PADA CABAI KERITING SECARA In Vitro - Ibnu Khairul; Vivi B. Montong; Max M. Ratulangi (COCOS, 2017)
ABSTRACT Â Colletotrichum capsici is one of the fungi that can cause anthracnose disease in chili plants. Trichoderma sp. is an antagonistic fungus that has the potential to control anthracnose disease. This study aims to determine the growth and development of the fungus Trichoderma sp. and Colletotrichum capsici pathogenic fungi as well as the percentage of inhibition of Trichoderma sp. fungus. against the Colletotrichum capsici fungus. Testing using dual culture method on Potato Dextrose Agar media to know the percentage of inhibition.The results of this study showed that the colony of Trichoderma sp. able to inhibit the growth of Colletotrichum capsici fungal colonies with an average percentage of 2.82% inhibition on the third day after inoculation; 70.28% on the fourth day after inoculation and 100% on the fifth day after inoculation. Â Keywords: Percentage, Colletotrichum capsici, Anthracnose